Alpha beta-crystallin expression and presentation following infection with murine gammaherpesvirus 68. (15th April 2013) - Chauhan, Vinita S.; Nelson, Daniel A.; Marriott, Ian; Bost, Kenneth L.
Abstract: Alpha beta-crystallin (CRYAB) is a small heat shock protein that can function as a molecular chaperone and has protective effects for cells undergoing a variety of stressors. Surprisingly, CRYAB has been identified as one of the dominant autoantigens in multiple sclerosis. It has been suggested that autoimmune mediated destruction of this small heat shock protein may limit its protective effects, thereby exacerbating inflammation and cellular damage during multiple sclerosis. It is not altogether clear how autoimmunity against CRYAB might develop, or whether there are environmental factors which might facilitate the presentation of this autoantigen to CD4+ T lymphocytes. In the present study, we utilized an animal model of an Epstein Barr Virus (EBV)-like infection, murine gammaherpesvirus 68 (HV-68), to question whether such a virus could modulate the expression of CRYAB by antigen presenting cells. Following exposure to HV-68 and several other stimuli, in vitro secretion of CRYAB and subsequent intracellular accumulation were observed in cultured macrophages and dendritic cells. Following infection of mice with this virus, it was possible to track CRYAB expression in the spleen and in antigen presenting cell subpopulations, as well as its secretion into the blood. Mice immunized with human CRYAB mounted a significant immune response against this heat shock protein. Further, dendritic cells that were exposed to HV-68 could stimulate CD4+ T cells from CRYAB immunized mice to secrete interferon gamma. Taken together these studies are consistent with the notion of a gammaherpesvirus-induced CRYAB response in professional antigen presenting cells in this mouse model.